2023
DOI: 10.3390/su15031907
|View full text |Cite
|
Sign up to set email alerts
|

Research on Green and Low-Carbon Rural Development in China: A Scientometric Analysis Using CiteSpace (1979–2021)

Abstract: Green and low-carbon rural development (GLRD) is becoming an important way to explore sustainable development in rural areas of China. It is significant for the sustainable development of the rural economy and of society to build a rural carbon sink system, advocate low-carbon emissions in rural areas, and promote the development of rural green industries and rural transformation. In this study, the existing knowledge system of GLRD was analyzed using CiteSpace. Keywords related to GLRD and their occurrence fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…With the aging of the rural population, there has been a marked increase in carbon emissions resulting from residential energy consumption [32]. Scholars have observed that between 2012 and 2018, per capita carbon emissions in rural areas increased, even though overall emissions declined [33]. Presently, research strategies for reducing rural carbon emissions primarily focus on enhancing the carbon sequestration capabilities of rural ecosystems (such as forests, wetlands, and farmlands) and curbing carbon emissions from rural residential living.…”
Section: Rural Carbon Emissionsmentioning
confidence: 99%
“…With the aging of the rural population, there has been a marked increase in carbon emissions resulting from residential energy consumption [32]. Scholars have observed that between 2012 and 2018, per capita carbon emissions in rural areas increased, even though overall emissions declined [33]. Presently, research strategies for reducing rural carbon emissions primarily focus on enhancing the carbon sequestration capabilities of rural ecosystems (such as forests, wetlands, and farmlands) and curbing carbon emissions from rural residential living.…”
Section: Rural Carbon Emissionsmentioning
confidence: 99%
“…However, combing through the relevant literature reveals that scholars have mostly focused on the principles of inorganic carbon and carbon storage, and there is a lack of a separate discussion on the research trends of soil inorganic carbon sink. On the other hand, in recent years, research hotspots and trends in a certain research area are often realized by CiteSpace software, which is more intuitive and more scientific in showing the current situation and future trends of research in the field, it has been widely used in different research fields in China and abroad, and is one of the more mature research tools available [9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…This Issue also includes a spatial analysis example for an economic model which study's the spatiotemporal interaction between Kinjiangls county transformation over 10 years [27]. The second issue discussed is environmental elements modelling, covering a nonlinear model enabling the reconstruction of missing meteorological data [28], green and low-carbon rural development metanalyses with the use of graph analysis [29], and PM 2.5 and PM 10 prediction modelling with the use of a nonlinear autoregressive exogenous model [30]. The third topic is an issue of purifying the environment polluted by humans with the use of living organisms [31] and the analysis of the effectiveness of testing the level of its cleaning [32].…”
mentioning
confidence: 99%